2015
DOI: 10.1007/s40291-015-0133-8
|View full text |Cite
|
Sign up to set email alerts
|

Poorly Differentiated Neoplasms of Unknown Primary Site: Diagnostic Usefulness of a Molecular Cancer Classifier Assay

Abstract: The MCCA provided a specific lineage diagnosis and tissue of origin in most patients with PDNs unclassifiable by standard pathologic evaluation. Earlier use of MCCA will expedite diagnosis and direct appropriate first-line therapy, which is potentially curative for several of these tumor types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…Rossi et al (2015) observed higher frequencies, in descending order, of non-determined neoplasms for carcinomas, sarcomas, melanomas, and mastocytomas but no cases of lymphoma. This information is corroborated by recent studies in human patients (GRECO et al, 2015), in which lymphoma was the less diagnosed neoplasm of unknown origin.…”
Section: Case Reportsupporting
confidence: 77%
“…Rossi et al (2015) observed higher frequencies, in descending order, of non-determined neoplasms for carcinomas, sarcomas, melanomas, and mastocytomas but no cases of lymphoma. This information is corroborated by recent studies in human patients (GRECO et al, 2015), in which lymphoma was the less diagnosed neoplasm of unknown origin.…”
Section: Case Reportsupporting
confidence: 77%
“…Based on this assumption, molecular methods using gene expression profiling, gene microarrays, microRNA, and DNA methylation analysis are increasingly employed as classifier assays to predict the TOO. Conceptually, the TOO classifiers are trained on a database of TOO-specific molecular signatures established by analyzing primaries of known origin and can predict the TOO of known primaries with accuracies of 76-96% (29)(30)(31)(32)(33)(34)(35). As already pointed out elsewhere, an important limitation of this approach is the number of different tumor types used in training the TOO classifier (36).…”
Section: Chasing the Tissue Of Origin (Too) In Cupmentioning
confidence: 99%
“…Gene expression profiling is an effective approach in identifying the primary tumor site in CUP [ 78 ]. The expression levels of messenger RNA (mRNA) or micro-RNA (miRNA) can be assessed using reverse-transcription polymerase chain reaction (RT-PCR) or oligonucleotide microarray technology [ 79 , 80 ].…”
Section: Histopathological Diagnosismentioning
confidence: 99%
“…The expression levels of messenger RNA (mRNA) or micro-RNA (miRNA) can be assessed using reverse-transcription polymerase chain reaction (RT-PCR) or oligonucleotide microarray technology [ 79 , 80 ]. Currently, two commercially available assays capable of identifying the primary tumor in approximately 80% of cases are available [ 78 , 81 ]. The clinical utility of these assays is supported by the results of a phase II trial, suggesting a survival benefit in patients treated with site-specific therapy based on a gene expression profile [ 81 ]; moreover, the results of a phase III trial addressing this issue (GEFCAPI 04) are incoming [ 82 ].…”
Section: Histopathological Diagnosismentioning
confidence: 99%